Generational renewal in agriculture: Bibliometric analysis - Daniela Nicoleta Bădan (Voicilă) (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. International Symposium. 11th Edition, 2020)
In recent decades, the number of young farmers has declined in most developed countries. This issue has been debated and recognized by scientists and policy makers. Despite all the support measures implemented at European level and abroad, young farmers continue to face barriers that prevent both the establishment and consolidation of the agricultural holdings taken over. All these existing policy support measures for young farmers are seen as triggers and determinants in the process of renewing generations of farmers. The main purpose of this study is to examine the existing situation of research conducted at European level and outside its borders on the generational renewal of farmers. During the paper, a bibliometric analysis of the research papers registered in the Web of Science database was performed, starting from the previously proposed topic. The analysis software used was VOSviewer, thus creating a descriptive part of the stored information, presenting an overview of the proposed research topic by viewing the connections created. This study reveals that this topic has been comprehensively studied in recent years in various fields.
Keywords: Q01; Q18; 330; generational renewal; young farmers; bibliometric analysis